Japanese Encephalitis Outbreak in South-Eastern Australia, 2022 - Danielle Hutchinson; Mohana Kunasekaran; Xin Chen; Aye Moa (University of New South Wales, 2022)
In February and March 2022, an outbreak of Japanese Encephalitis Virus (JEV) was detected in piggeries in southern Queensland, NSW, Victoria and South Australia. Subsequently, human cases of JEV have been confirmed in each of the affected states, with 35 confirmed or probable cases and 3 deaths as of 7 April 2022. This is the first JEV outbreak in mainland Australia. JEV has not been detected in mosquitos, animals or humans in south-Eastern Australia previously and question remain about how it became established, and whether it will become endemic to this region. The majority of cases are occurring around the affected piggeries where there is exposure to mosquitoes, particularly in the older age group, and vaccination has commenced in this population.